SiO2/TiO2 Composite Coating on Light Substrates for Photocatalytic Decontamination of Water - Hana Bíbová; Lenka Hykrdová; Hiep Hoang; Milan Eliáš; Jaromír Jirkovský (Journal of Chemistry)
In this study, we describe synthesis and characterization of a floating photocatalyst for water treatment consisting of a light substrate coated by SiO2/TiO2 composite. Three supports of natural origin were used: natural cork, expanded clay (Liapor), and volcanic porous glass (Sorbix). The photoactivity of the coated supports was tested in a laboratory photoreactor, with Liapor being the most photoactive support with good mechanical stability. The corresponding rate constant for the degradation of a model pollutant, 4-chlorophenol, was 7.8 × 10−5 s−1. Detail characterization of the coated Liapor was obtained by XRF, SEM/EDX, and UV-Vis diffuse reflectance spectroscopy, and surface area measurements. Outdoor experiments were carried out with calcined Liapor and oxalic acid or methylene blue under sunlight on pilot reactors in the Czech Republic and Vietnam. We demonstrated satisfactory photocatalytic activity, long-term stability, and reusability of the new floating photocatalyst. The photoefficiency to mineralize oxalic acid in water under sunlight was estimated as 6.7% under the applied conditions.